A two-tiered approach to the valuation of investment projects adjusted for governance risk - Rodolfo Apreda (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2009)
This paper sets forth a pair of distinctive contributions to the subject. In the first place, it provides a unified approach to capital investment decisions, by means of a two-tiered framework of analysis. Such approach consists in working out the net present value of the project by discounting its cash flows with a temporal structure of rates of return adjusted for country and credit risk; this procedure accounts for the first tier. It is for the second tier to bring about both the internal and external rates of return. Afterwards, we broaden the streamlined viewpoint in valuation by introducing the Corporate Governance risk rate. As a byproduct, the paper also attempts to furnish analysts as well graduate students taking core courses on Corporate Finance with a friendly and easier road to valuation.
Keywords: G30; G31; G34; 330; investment valuation; net present value; investment projects; internal rate of return; external rate of return; governance risk; cost of capital; Betriebliche Investitionstheorie; Investitionsrechnung